Understanding violence within protest: a case study investigation of the Rhodes Must Fall Movement at the University of Cape Town (2015 2016) - Motimele, Mapheyeledi (Division of Occupational Therapy, 2025)
South Africa is regarded as one of the most violent countries in the world. This statement is supported by news reports and crime-statistics both locally and internationally, despite contestation as to what exactly constitutes ‘violence', including, how it manifests in South Africa and what it may be an expression of. Further to this, South Africa has also gained a reputation for being the protest capital of the world, with many of these labelled as ‘violent'. South Africa's legacy of ‘violent' protest has endured throughout the country's Colonial-Apartheid history and continues, despite a transition to a democratic state in 1994. Despite the prevalence of this phenomenon, there has been little done by way of research to understand how and why ‘violence' and protest continue to occur both in and of each other and remain characteristic of the South African context. The Rhodes Must Fall (RMF) movement at the University of Cape Town (UCT) in 2015-2016, was criticized for enacting ‘violent' forms of protest. Conversely, student activists, staff, and workers within RMF, surfaced institutional racism and patriarchy at the university as ‘violence(s)' black people continued to be subjected to, as evidence of coloniality within the institution. These seemingly opposed perspectives of violence in the context of protest informed the selection of RMF at UCT (2015-2016) as a case. This study was particularly concerned with the various ways ‘violence' manifested during the RMF protests at UCT and the conditions that might explain how it found expression, shifting focus from the act of violence to the less investigated structures, relations, practices, and processes that manifested ‘violence'. Further to this, the discipline of occupational science (OS) and profession of occupational therapy (OT) have yet to investigate violence within protest from an occupational perspective, despite the global prevalence of these co-occurring phenomena and their impact on individual and collective health and wellbeing. This study aimed to describe and explain both the manifestation and expression of violence during RMF at (UCT) 2015-2016. The case was investigated within a Qualitative research design and informed by a Critical-Decolonial perspective. This study adopted a Case-Study approach and incorporated Narrative Inquiry methods to gain a comprehensive understanding of what RMF was a case about, for and of. Data sources included narrative interviews and key informant interviews, photos of physical artefacts and the review of relevant archives and documents. Data was analyzed using narrative analysis and a thematic framework approach. Findings are presented in the form of five student activists' stories and a comprehensive case-narrative. Violence during RMF at UCT (2015-2016) was revealed as a process through which coloniality was applied and/or resisted. Furthermore, violence manifested as context (characterized by coloniality), as protest (preceded and provoked by coloniality) and as denial of coloniality. These manifestations of violence within the RMF protests were read as expressions of colonial sovereignty and an intention to heal/reclaim being through protest as an enactment of occupational role subversion. Lastly the consequences for participation in RMF for the health and wellbeing of student activists, revealed experiences of criminalization and punishment characteristic of South Africa's Colonial-Apartheid history of repression of protest, calling for a reframing of health and wellbeing as a synthesis of access, representation, and agency. The study findings indicate the need to a) further investigate violence within protest from an occupational perspective, b) revisit and critique core philosophies, concepts and theories of human occupation, health, and wellbeing from a critical-decolonial perspective and c) interrogate the role and scope of occupational therapy as it pertains to the duty of care the profession carries towards activists as potential service-users.